Muscle thickness of serratus anterior muscle during performing wall push-up plus and standard push-up plus using ultrasound imaging - Wannaprom, Nipaporn; Onket, Kamonjutha; Puachaikul, Jakkapop; Uthaikhup, Sureeporn (Journal of Associated Medical Sciences, 2017)
Background: Serratus anterior exercise is an important rehabilitation program in clinical practices. Different positions may affect muscle activity. However, there has no report investigating the thickness of serratus anterior during contraction in different positions. Objectives: To investigate thickness of serratus anterior muscle at rest compare to during performing wall push-up plus and standard push-up plus. Materials and methods: Twenty healthy male volunteers were participated. Thickness of right serratus anterior muscles was measured using ultrasound under three conditions: at rest, wall push-up plus and standard push-up plus. Each condition was repeated three times. Each image of serratus anterior muscle was measured three times by Image J software. Results: Thickness of serratus anterior muscle during performing wall push-up plus and standard push-up plus were greater than at rest (p<0.001). There was no significant difference in thickness of serratus anterior muscle between wall push-up plus and standard push-up plus positions (p>0.05). Conclusion: Thickness of serratus anterior muscle during performing wall push up plus and standard push up is not different. This suggests that both wall push-up plus and standard push-up can be applied to enhance performance of serratus anterior muscle.